2001 Conference Proceedings of the 23rd Annual International Conference of the IEEE Engineering in Medicine and Biology Society
DOI: 10.1109/iembs.2001.1020408
|View full text |Cite
|
Sign up to set email alerts
|

Finite element modeling of intermuscular interactions and myofascial force transmission

Abstract: Abstract-A finite element muscle model to study the principles of intermuscular myofascial force transmission is developed. The results obtained explain force differences at the distal and proximal tendons of muscles that have mechanical interaction. This is in agreement with experimental findings in other recent studies. The strain distributions found along the fiber direction indicate intermuscular myofascial force transmission. A consequence is that active force generated within one muscle may be exerted at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 14 publications
2
9
0
Order By: Relevance
“…Such transmission is an important determinant of the distribution of sarcomere lengths in series within muscle fibers. Results of a finite element modeling study on isolated muscle (Yucesoy et al, 2002) support this conclusion. In that work it was demonstrated that if there is an inadequate linking of sarcomeres to the extracellular matrix (as occurs in muscular dystrophies), at high muscle lengths the myofibers may be deformed beyond physiological limits.…”
Section: Distribution Of Length Of Sarcomeres Arranged In Series Withsupporting
confidence: 71%
See 4 more Smart Citations
“…Such transmission is an important determinant of the distribution of sarcomere lengths in series within muscle fibers. Results of a finite element modeling study on isolated muscle (Yucesoy et al, 2002) support this conclusion. In that work it was demonstrated that if there is an inadequate linking of sarcomeres to the extracellular matrix (as occurs in muscular dystrophies), at high muscle lengths the myofibers may be deformed beyond physiological limits.…”
Section: Distribution Of Length Of Sarcomeres Arranged In Series Withsupporting
confidence: 71%
“…Transmission of the force generated by the sarcomeres, from the full perimeter surface of the myofibers onto the extracellular matrix has been emphasized by some authors (e.g., Street, 1983;Danowski et al, 1992;Trotter & Purslow, 1992;Hijikata et al, 1993;Huijing et al, 1998;Huijing, 1999a;Yucesoy et al, 2002). Such transmission was referred to as myofascial force transmission (Huijing, 1999b).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations